2014
DOI: 10.1515/vfzg-2014-0027
|View full text |Cite
|
Sign up to set email alerts
|

Demokratie und Wirtschaftspolitik in der Weimarer Republik

Abstract: 569Weimar, das lange von der Forschungsagenda verschwunden war, erlebt neuerdings eine Art Renaissance. Im Mittelpunkt steht dabei nicht mehr das Problem einer "Demokratie ohne Demokraten", die fast unweigerlich zum Scheitern verurteilt war. Der Fokus richtet sich jetzt auf die gegenläufigen Kräfte -auf die zunehmende Zahl der Demokraten und ihre vielversprechenden Reformkonzepte, die immer mehr Anklang fanden und so oder so ähnlich auch in den USA und anderen europäischen Staaten diskutiert wurden. Weimar, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An interesting fact is that the UK legislator also concluded that there is no need to conclude a written contract, but employers often follow traditions, because otherwise, it is obliged to notify the employee in writing about the terms of employment (https://base.garant.ru). US legislation also lacks a mandatory requirement for a written form of an employment contract (with the exception of the employment of seafarers), however, there are three possible forms of it: written, oral and implied (MULLER, 2014). In turn, the conclusion of an oral contract naturally does not imply the observance of guarantees (even about the time of commencement of work and their payment).…”
Section: Methodsmentioning
confidence: 99%
“…An interesting fact is that the UK legislator also concluded that there is no need to conclude a written contract, but employers often follow traditions, because otherwise, it is obliged to notify the employee in writing about the terms of employment (https://base.garant.ru). US legislation also lacks a mandatory requirement for a written form of an employment contract (with the exception of the employment of seafarers), however, there are three possible forms of it: written, oral and implied (MULLER, 2014). In turn, the conclusion of an oral contract naturally does not imply the observance of guarantees (even about the time of commencement of work and their payment).…”
Section: Methodsmentioning
confidence: 99%
“…As is shown by Müller's (2014) analysis of the Ministry of Economics, not all ministries were opposed to socialist or Keynesian policies. Nonetheless, even the labor ministry, dominated by socialists and trade unions, was taken over by conservative bureaucrats from 1924 (Liu 1997: 363).…”
Section: The Formation Of Bureaucratic Quality In Prussia and Germanymentioning
confidence: 99%